MST1 Suppresses Disturbed Flow Induced Atherosclerosis. Issue 9 (27th September 2022) - Quan, Meixi; Lv, Huizhen; Liu, Zening; Li, Kan; Zhang, Chenghu; Shi, Lei; Yang, XinYu; Lei, Ping; Zhu, Yi; Ai, Ding
Abstract : Background: Atherosclerosis occurs mainly at arterial branching points exposed to disturbed blood flow. How MST1 (mammalian sterile 20-like kinase 1), the primary kinase in the mechanosensitive Hippo pathway modulates disturbed flow induced endothelial cells (ECs) activation and atherosclerosis remains unclear. Methods: To assess the role of MST1 in vivo, mice with EC-specific Mst1 deficiency on ApoE −/− background ( Mst1 iECKO ApoE −/− ) were used in an atherosclerosis model generated by carotid artery ligation. Mass spectrometry, immunoprecipitation, proximity ligation assay, and dye uptake assay were used to identify the functional substrate of MST1. Human umbilical vein endothelial cells and human aortic endothelial cells were subjected to oscillatory shear stress that mimic disturbed flow in experiments conducted in vitro. Results: We found that the phosphorylation of endothelial MST1 was significantly inhibited in oscillatory shear stress-exposed regions of human and mouse arteries and ECs. Ectopic lenti-mediated overexpression of wild-type MST1, but not a kinase-deficient mutant of MST1, reversed disturbed flow-caused EC activation and atherosclerosis in EC-specific Mst1 deficiency on ApoE −/− background ( Mst1 iECKO ApoE −/− ). Inhibition of MST1 by oscillatory shear stress led to reduced phosphorylation of Cx43 (connexin 43) at Ser255, the Cx43 hemichannel open, EC activation, and atherosclerosis, which were blocked by TAT-GAP19, a Cx43 hemichannel inhibitory peptide. Mass spectrometry studies identified that Filamin B fueled the translocation of Cx43 to lipid rafts for further hemichannel open. Finally, lenti-mediated overexpression of the Cx43 S255 mutant into glutamate to mimic phosphorylation blunted disturbed flow-induced EC activation, thereby inhibiting the atherogenesis in both ApoE −/− and Mst1 iECKO ApoE −/− mice. Conclusions: Our study reveals that inhibition of the MST1-Cx43 axis is an essential driver of oscillatory shear stress-induced endothelial dysfunction and atherosclerosis, which provides a new therapeutic target for the treatment of atherosclerosis.